Authenticity and Provenance in Long-Term Digital Preservation: Analysis of the Scope of Content - Varnienė-Janssen, Regina; Kuprienė, Jūratė (Information & Media, 2018)
[full article, abstract in English; abstract in Lithuanian]Authenticity is a fundamental issue for the long-term preservation of digital objects; however, the validation of authenticity is a complex task – it requires the representation of provenance as a precondition for trust. For that matter, it is crucial to define the key conceptual elements that provide the foundation for such a complex framework. The main objective of this paper is to define how authenticity has to be managed in the digital preservation process: to identify the semantic units needed to support core preservation functions in order to ensure the trustworthiness of digital objects and ensure interoperability – i.e., the ability to exchange data between institutions. This paper presents results from the first stage of the research: the scope of authenticity and provenance content needed to support core preservation functions and ensure interoperability – the ability to exchange data between institutions and assess the added value of the Europeana and VEPIS regarding authenticity and provenance based on the adequacy of analyzed international models for authenticity and provenance.Methodology: by applying the EU 2–3–6 concept of added value for electronic publishing and qualitative content analysis of research literature, we conceptualized the Content Creation Process, which refers to the structure and meaning of authenticity and provenance. This approach enabled us to identify the scope of the content of authenticity and provenance.
Keywords: authenticity; provenance; trust; digital environment; data quality; trustworthiness of digital objects; Lithuania’s Information System of Virtual Electronic Heritage (VEPIS); Europeana